Flight dynamics and control of aero and space vehicles - Yedavalli, Rama K. (John Wiley & Sons, Inc., 2020)
Flight Vehicle Dynamics and Control Rama K. Yedavalli, The Ohio State University, USA A comprehensive textbook which presents flight vehicle dynamics and control in a unified framework Flight Vehicle Dynamics and Control presents the dynamics and control of various flight vehicles, including aircraft, spacecraft, helicopter, missiles, etc, in a unified framework. It covers the fundamental topics in the dynamics and control of these flight vehicles, highlighting shared points as well as differences in dynamics and control issues, making use of the 'systems level' viewpoint. The book begins with the derivation of the equations of motion for a general rigid body and then delineates the differences between the dynamics of various flight vehicles in a fundamental way. It then focuses on the dynamic equations with application to these various flight vehicles, concentrating more on aircraft and spacecraft cases. Then the control systems analysis and design is carried out both from transfer function, classical control, as well as modern, state space control points of view. Illustrative examples of application to atmospheric and space vehicles are presented, emphasizing the 'systems level' viewpoint of control design. Key features: Provides a comprehensive treatment of dynamics and control of various flight vehicles in a single volume. Contains worked out examples (including MATLAB examples) and end of chapter homework problems. Suitable as a single textbook for a sequence of undergraduate courses on flight vehicle dynamics and control. Accompanied by a website that includes additional problems and a solutions manual. The book is essential reading for undergraduate students in mechanical and aerospace engineering, engineers working on flight vehicle control, and researchers from other engineering backgrounds working on related topics
Keywords: Flight control.; Airplanes -- Control systems.; Space vehicles -- Dynamics.; Space vehicles -- Control systems.; Space vehicles -- Command control systems.; elektronické knihy; electronic books